Weekly administration of docetaxel in combination with estramustine and celecoxib in patients with advanced hormone-refractory prostate cancer: final results from a phase II study - Carles, J (Nature Publishing Group, 2007)
The objective of this study was to evaluate the efficacy and safety profile of weekly docetaxel, estramustine and celecoxib in patients with advanced hormone-refractory prostate cancer. Forty-eight patients received 35 mg m(−2) of weekly docetaxel for 3 out of every 4 weeks, 280 mg of estramustine twice daily on days 1–3, 8–10, 15–17 and 400 mg of celecoxib twice daily until progression or toxicity. Cycles were repeated every 28 days for at least six cycles. Patients were evaluated for response and toxicity. Patients received a median of four cycles (range: 1–9). On an intention-to-treat analysis, prostate-specific antigen (PSA) was decreased greater than 50% in 28 out of 48 patients (overall response rate: 58%, 95% confidence interval (CI): 44–72) and median duration of PSA response was 8.0 months (95% CI: 6.9–9.0). After a median follow-up of 11.3 months, the median time to progression was 7.1 months and the median overall survival was 19.2 months. The most frequent severe toxicity was asthenia (15% of patients), diarrhoea and stomatitis (8% of patients, each). Grade 3/4 neutropenia was reported in two patients. There was a toxic death during the study due to a gastric perforation. Celecoxib with weekly docetaxel and estramustine is an effective and safe treatment for patients with hormone-refractory prostate cancer, but it does not seem to add any benefit to docetaxel.